Missions remembered : recollections of the World War II air war - Middle Tennessee WWII Fighter Pilots Association (New York : McGraw-Hill, 1998)
From bailouts to belly landings, flaming cockpits to lurching carrier decks, here are heroic tales of pilots from all backgrounds, united by a desire to fight their country's enemy to the finish. Drawn from a small corner of Tennessee, these men flew in all theatres of combat, in every front-line fighter aircraft. A memorable anthology of combat tales with great appeal both for veterans and historians. 28 illustrations.
Roland H. Baker -- E.H. Bayers -- George M. Blackburn -- Roy B. Broster Jr. -- Bill Burch -- Johnnie B. Corbitt -- Frank Davis -- Herman K. Freeman -- Lee V. Gossick -- Robert F. Hahn -- Clifford J. Harrison Jr. -- Edward F. Jones -- David C. Kipp -- Beverly W. Landstreet III -- J. Pat Maxwell -- Dutch McMillin -- William S. Miller -- Charles R. Mott -- Eugene D. Pargh -- Ernest C. Perry -- William Pickron Jr. -- William A. Potts -- O.T. Ridley -- William T. Sellers -- William Shawb -- Roy D. Simmons Jr. -- Enoch B. Stevenson Jr. -- Joe Thompson Jr. -- Leslie Traughber -- William W. Wells -- Kenneth West -- W.S. Whitmore -- Hensley Williams.
Includes index.
Keywords: 1939 - 1945; World War, 1939-1945 -- Aerial operations, American; Fighter pilots -- Tennessee -- Biography; World War, 1939-1945 -- Personal narratives, American; Pilotes de chasse -- Tennessee -- Biographies; Military operations, Aerial -- American; Fighter pilots; Luchtmacht; World War, 1939-1945 -- Aerial operations, American; Fighter pilots -- United States -- Tennessee -- Biography; Middle Tennessee WWII Fighter Pilots Association; Tennessee; collective biographies; Personal narratives; Biographies; Personal narratives -- American; Biographies; Personal narratives; Biographies; 2